2002
DOI: 10.3354/meps244139
|View full text |Cite
|
Sign up to set email alerts
|

Seascape biodiversity patterns along the Mediterranean and the Black Sea: lessons from the biogeography of benthic polychaetes

Abstract: The purpose of this paper is to investigate seascape biodiversity patterns along the Mediterranean and the Black Sea through the study of the benthic polychaete biogeography of the region. A set of non-parametric multivariate analyses and recently developed diversity indices were performed on the benthic polychaete inventories of the areas of the Mediterranean and the Black Sea. Both the numbers of species and the multivariate analyses demonstrate a west-east zoogeocline, shown by the decreasing number of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 41 publications
10
50
0
1
Order By: Relevance
“…Thus, the Aegean Sea ranks third in the Mediterranean in terms of demosponge diversity, following the western Mediterranean (80%) and the Adriatic (40%), although until recently its sponge fauna was considered underestimated (Pansini et al 2000). This scaling agrees with that for the Mediterranean octocorals (Vafidis et al 1994) and amphipods (Stefanidou and Voultsiadou 1995), but other groups such as decapods (Koukouras et al 1992), ascidians (Koukouras et al 1995), gastropods (Koutsoubas et al 1997) and polychaetes (Arvanitidis et al 2002) are represented by higher species numbers in the Aegean than in the Adriatic Sea.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Thus, the Aegean Sea ranks third in the Mediterranean in terms of demosponge diversity, following the western Mediterranean (80%) and the Adriatic (40%), although until recently its sponge fauna was considered underestimated (Pansini et al 2000). This scaling agrees with that for the Mediterranean octocorals (Vafidis et al 1994) and amphipods (Stefanidou and Voultsiadou 1995), but other groups such as decapods (Koukouras et al 1992), ascidians (Koukouras et al 1995), gastropods (Koutsoubas et al 1997) and polychaetes (Arvanitidis et al 2002) are represented by higher species numbers in the Aegean than in the Adriatic Sea.…”
Section: Discussionsupporting
confidence: 77%
“…Various invertebrate groups demonstrate this trend of decreasing endemism in the Mediterranean from west to east (Koukouras et al 2001). However, Arvanitidis et al (2002) did not find differences in the distribution of the zoogeographical categories of polychaetes among the Mediterranean areas. It is worth mentioning that none of the four Indo-Mediterranean species that entered the Levantine basin as lessepsian migrants (Tsurnamal 1969b) have been up-to-now found in the Aegean Sea.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…the greater the species richness of a taxon for a particular habitat, the greater its sensitivity to changes in biological or environmental gradients. however, results have also demonstrated that each taxon (phylum level) might respond very differently to the others as consequence of its local representativeness, its relative composition of motile or sessile forms, its evolutionary history for that habitat and the potential breadth of its taxonomic/phylogenetic tree (Arvanitidis et al, 2002;Glasby, 2005). the notable occurrence of sessile filter-feeding species upon the shells of Pinna can support the possible existence of competition for nutrients, since the two parts belong to the same trophic guild.…”
Section: Spatial and Taxonomic Species Turnover The Contribution Of mentioning
confidence: 96%
“…Email: Francois.Schmitt@univ-lille1.fr (Knox 1977) and one of the richest invertebrate benthic taxa with regard to species number (Arvanitidis et al 2002). This group, which often dominates benthic macrofauna (Grémare et al 1998), is known to comprise mainly 60-70% of macrozoobenthic individuals on soft bottoms (Knox 1977;Dogan et al 2005), and can be used as 'markers' of different ecological conditions (Gambi & Giangrande 1986).…”
Section: Introductionmentioning
confidence: 99%